ANALYSIS OF THE CONTENT OF IMMUNE COMPLEXES IN BLOOD MILK IN PATIENTS WITH MULTIPLE SCLEROSIS WITH PATHOGENETIC AND DISEASE CHARACTERISTIC THERAPY - Boychuk, M. O.; Bilyy, R. O.; Nehrych, T. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In order to determine the activity of multiple sclerosis (MS), in particular for the objective confirmation of exacerbation of the disease, it is proposed to conduct a test for analyzing the antibody to the main myelin protein (OBM) and determining the antibodies to the components of the secondary non-necrotic cells (SNEC).